2002
DOI: 10.1046/j.1365-2486.2002.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe drought effects on ecosystem CO2 and H2O fluxes at three Mediterranean evergreen sites: revision of current hypotheses?

Abstract: Eddy covariance and sapflow data from three Mediterranean ecosystems were analysed via top‐down approaches in conjunction with a mechanistic ecosystem gas‐exchange model to test current assumptions about drought effects on ecosystem respiration and canopy CO2/H2O exchange. The three sites include two nearly monospecific Quercus ilex L. forests – one on karstic limestone (Puéchabon), the other on fluvial sand with access to ground water (Castelporziano) – and a typical mixed macchia on limestone (Arca di Noè). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
333
4
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 503 publications
(366 citation statements)
references
References 106 publications
23
333
4
6
Order By: Relevance
“…Davidson et al (1998) reported that Q 10 for soil respiration ranged from 3.4 to 5.6 for different study sites in a temperate mixed hardwood forest. Considering variations in soil moisture, Reichstein et al (2002b) reported a significant decline in Q 10 (from 0.5 to 2.6) when the soil moisture dropped for three Mediterranean evergreen sites.…”
Section: Response Of Nighttime F C To Temperaturementioning
confidence: 93%
“…Davidson et al (1998) reported that Q 10 for soil respiration ranged from 3.4 to 5.6 for different study sites in a temperate mixed hardwood forest. Considering variations in soil moisture, Reichstein et al (2002b) reported a significant decline in Q 10 (from 0.5 to 2.6) when the soil moisture dropped for three Mediterranean evergreen sites.…”
Section: Response Of Nighttime F C To Temperaturementioning
confidence: 93%
“…To a certain extent, carbon storage in forests buys time, until we find more definitive solutions to our dependency on energy from fossil fuel. However, forests can easily become carbon sources rather than carbon sinks (Kurz and Apps, 1999, Gracia et al, 2001, Reichstein et al, 2002. Changes in the regimes of natural disturbances such as fire, pests or drought (Fuhrer et al, 2006, Sohngen et al, 2005, Ciais et al, 2005, can affect major forest functions, forestry outputs and forest stability.…”
Section: Strategies To Improve Carbon Sequestrationmentioning
confidence: 99%
“…The function f 1 is based on the work of Tjoelker et al [2001], and f 2 is based on the work of Reichstein et al [2002], where b 1 is a biome-dependent model parameter (μmol m À2 s À1 ) and the empirical constants b 2 , b 3 , T s0 , and θ s0 are equal to 52.4 (K), 285 (K), 227.2 (K), and 0.16, respectively Reichstein et al [2002]. T avg is the annual mean soil temperature (K) and is assumed to be equal to the temperature of the deepest soil layer (T s,6 ).…”
Section: A12 Net Canopy Photosynthesismentioning
confidence: 99%